(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Improvements in dental health, function, beauty, and self-esteem are widely acknowledged advantages of orthodontic treatment. An economic evaluation of orthodontic treatment forms the basis for decision-making planning and management of dental care. Aim: This study aims to estimate the perception of patients seeking orthodontic treatment categorized according to age, education, and family income and to identify barriers that prevent them from considering treatment. Methodology: Proforma was sent to dental colleges and specific clinics from metro, urban and rural areas across India. 500 patients seeking orthodontic treatment took part in the survey. Data was collected and analyzed statistically. Results: Cost was the main factor, which patients felt was responsible for not completing treatment or preventing them to consider the treatment. All patients felt that a good smile should be included in the Right to Health by Government and steps should be taken to make this treatment accessible for all.